159 A Crucial Role of Nox2-Derived Reactive Oxygen Species in Ageing-Associated Metabolic Disorders and Brain Oxidative Damage. (3rd June 2016) - Geng, Li; Li, Jian-Mei
Abstract : Ageing has been recognised to be a major risk factor for the development of cardiovascular and neurodegenerative diseases and growing evidence suggests a role for oxidative stress. A Nox2-containing NADPH oxidase has been reported to be a major source of reactive oxygen species (ROS) generation in the vascular system and in the brain. However, the role of Nox2 enzyme in ageing-related metabolic disorders and vascular neurodegeneration remains unclear. In this study, we used age-matched wild-type (WT) and Nox2-deficient (Nox2 -/- ) mice on a C57BL/6 background at young (3–4 month) and ageing (20–24 month) to investigate the role of Nox2 in ageing-related oxidative stress, metabolic disorders and cerebral vascular dysfunction. There was an ageing-related increase in blood pressure in WT mice (126 mmHg for young and 148 mmHg for ageing) (P < 0.05); however the blood pressure was well maintained without significant change in Nox2 -/- ageing mice. Compared to young WT mice, WT ageing mice had significantly high levels of fasting serum insulin and this was accompanied with delayed clearance of glucose (P < 0.05) indicating insulin resistance. In contrast, there was no indication of insulin resistance for Nox2 -/- ageing mice. We then examined ageing-related brain oxidative stress. Compared to WT young mice, there were significant increases (2.7 ± 0.7 folds) in the levels of ROS production by WT ageing brain tissue homogenates as detected by lucigenin-chemiluminescence and DHE fluorescence. Increased ROS production in WT ageing brain was accompanied by a significant increase (1.8 ± 0.3 folds) in the Nox2 expression detected mainly in the microglial cells (labelled by Iba-1) and decreases in brain capillaries (labelled by CD31) (2.4 ± 0.8 folds) and neurons (labelled by Neuronal Nuclei) (2.9 ± 0.5 folds) (all P < 0.05). Knockout Nox2 abolished ageing-associated increases in brain ROS production and reduced significantly the ageing-related pathophysiological changes in the brain. In conclusion, Nox2-derived oxidative stress plays an important role in ageing-associated metabolic disorders and vascular neurodegeneration. Nox2-containg NADPH oxidase represents a valuable therapeutic target for oxidative stress-related diseases in ageing.